2019
DOI: 10.3390/nu11020393
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene-Rich Extract from Red Guava (Psidium guajava L.) Decreases Plasma Triglycerides and Improves Oxidative Stress Biomarkers on Experimentally-Induced Dyslipidemia in Hamsters

Abstract: This work assessed the effects of a 28-day treatment with lycopene-rich extract (LRE) from red guava fruit (Psidium guajava L.) on the lipid profile and oxidative stress in an experimental model of dyslipidemia. Male hamsters (116.5 ± 2.16 g) were fed with the AIN 93G diet containing casein (20%), coconut fat (13.5%) and cholesterol (0.1%). The animals were divided into four groups: normolipidemic control (standard feed; NC, n = 7); hypercholesterolemic control (HC, n = 7); LRE 25 mg/kg/day (LRE-25, n = 7) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 57 publications
1
7
0
Order By: Relevance
“…The intraperitoneal and oral administration of a lycopene-rich extract from red guava (LEG) and lycopene purified from red guava (LPG) inhibit acute inflammation caused by carrageenan in Swiss mice at 50 and 12.5 mg/kg, respectively (Vasconcelos et al 2017). Furthermore, LEG treatment significantly reduces the viability of human breast adenocarcinoma cell (MCF-7) (IC 50 = 29.85 and 5.96 µg/mL at 24 and 72 h, respectively), as well as decreases the levels of plasma triglycerides and lipid peroxidation biomarkers in hamsters Silva Brito et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The intraperitoneal and oral administration of a lycopene-rich extract from red guava (LEG) and lycopene purified from red guava (LPG) inhibit acute inflammation caused by carrageenan in Swiss mice at 50 and 12.5 mg/kg, respectively (Vasconcelos et al 2017). Furthermore, LEG treatment significantly reduces the viability of human breast adenocarcinoma cell (MCF-7) (IC 50 = 29.85 and 5.96 µg/mL at 24 and 72 h, respectively), as well as decreases the levels of plasma triglycerides and lipid peroxidation biomarkers in hamsters Silva Brito et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, Kumar et al [219] observed that treatment with lycopene induced an increase in high-density lipoprotein and reduced levels of total cholesterol, LDL, triglycerides, and TBARS in rats fed a high-cholesterol diet. Brito et al [220] also demonstrated that lycopene extracted from guava (Psidium guajava L.) reduced MDA and triglyceride levels, as well as reduced plasma activity of myeloperoxidase and hepatic steatosis in an animal model of dyslipidemia. The results indicated that lycopene has hypolipidemic and anti-atherogenic potential.…”
Section: Anti-atherosclerotic Effect Of Lycopenementioning
confidence: 97%
“…Hypercholesterolemia was induced by feeding hamsters a high-cholesterol feed, according to Brito et al [ 25 ]. The effect caused by oral administration of LEG at doses of 25 mg/kg and 50 mg/kg on blood markers indicative of liver function in the animals was measured.…”
Section: Resultsmentioning
confidence: 99%
“…LEG and LPG presented a greater amount of lycopene than tomatoes, exhibited antimicrobial and antioxidant activities, and inhibited carrageenan-induced acute inflammation in mice [ 18 , 23 ]. The beneficial effects of LEG on human breast adenocarcinoma cells [ 24 ] and decreasing blood triglycerides and lipid peroxidation in hamsters fed a high-cholesterol diet [ 25 ] were also assessed.…”
Section: Introductionmentioning
confidence: 99%